ANALISIS BREAK EVEN POINT DENGAN PENDEKATAN MATEMATIKA MENGGUNAKAN MS. ACCESS PROGRAMMING - Suhartono, . (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
BreakevenAnalysis(break even point) is requiredfora companyat the time ofgoing toproducenew product/service. Dueto thebreakevenanalysis(break even point), it can be seenhow much the totalcostwill beincurredandwhat priceperunitis right forproducts/services.Knownas early as possiblewiththe selling priceperunit ofproduct/servicewillmake it easierfor companies tocalculatetheunit salesoccurkeberapabreakeven(break even point). Becausein additiontothe specificproductdesign, productionandplanningto maximizethe amount ofprofitthat isdesired, useone of the goalsistodetermine thebreakevenselling priceperunitso as toprevent theloss. One of the benefitsorusefulnessofbreak even pointof whichistoshowhowthe level of salesthat must be achieved, ifthe companywants tomake a profit. Thereare manykinds of costsbased onthe breakeven pointisa fixed cost, semifixedcosts, variable costsandsemi-variable costs. One of the assumptions/basicconceptsunderlying thebreak-even pointisall thecosts incurredin a companyshould beclassified intofixed costsandvariable costs. Thereare twomethods usedin the calculation ofbreakevenanalysisthatusesmathematicalapproachandgraphics. Keywords: Break EvenPoint, MathematicalApproach, Ms. AccessProgramming